High phenotypic and phytochemical diversity of Bactris gasipaes (Arecaceae) fruits in Ecuador - David Romero-Estévez; Thomas L.P. Couvreur; Michael Ayala; Eduardo Valarezo; Jorge G. Figueroa; María Judith Terán; Álvaro Rivera; Rommel Montúfar (PLoS ONE, 2026)
Climate change has negatively impacted food availability and nutritional quality. To address this challenge, it is essential to emphasize species that, despite their longstanding use by indigenous communities, remain underutilized or neglected. Integrating these culturally domesticated species into local food systems offers a promising strategy to improve access to healthy and sustainable foods. One such species is Bactris gasipaes Kunth, whose domesticated variety holds significant but largely untapped nutritional potential. Nevertheless, substantial gaps persist in our understanding of the morphological and phytochemical characteristics of its fruits. In the present study, 110 fruit samples of different Bactris gasipaes var. gasipaes individuals were analyzed to assess the proximal and biochemical composition of the mesocarp. Particular attention was given to the relationship between compositional traits and phenotypic characteristics, especially exocarp color. The results showed substantial intraspecific variation in fruit morphology and coloration, alongside notable nutritional values: crude protein (3.0–10.2%), crude fiber (0.2–3.0%), total oil (3.4–27.3%), tocopherols (<2.1 mg/g), β-carotene (<27.3 mg/100 g), and polyunsaturated fatty acids (4.7–44.1%). These results highlight the nutritional potential of B. gasipaes and its relevance for diversifying healthy food sources. Furthermore, results showed noticeable phytochemical differences and no strong correlations between specific components and phenotypic traits among fruit types in proximal parameters, nutritional content, and primary exocarp color, reinforcing the species’ value for food system integration. The observed diversity underscores the nutritional relevance of B. gasipaes from Ecuador and highlights the need for further research to classify fruit diversity for targeted use in food systems.